Large‐scale longitudinal climate gradient across the Palearctic region affects passerine feather moult extent. Issue 1 (8th October 2020) - Kiat, Yosef; Davaasuren, Batmunkh; Erdenechimeg, Tuvshinjargal; Troupin, David; Sapir, Nir
Abstract : Large‐scale spatial gradients of environmental conditions shape organisms, populations and ecosystems. Even though environmental gradients are a key research theme in macro‐ecology and biogeography, the effects of large‐scale, east–west, environmental gradients are largely overlooked compared with north–south gradients. Our study focused on feather moult, an important and energy demanding process in birds. By comparing Western and Eastern Palearctic populations of 21 species, we found that juvenile passerines in the Western and Eastern Palearctic differ in the number of feathers moulted as part of their post‐juvenile moult. This difference is most likely the result of a large‐scale climatic gradient in cold season duration and consequent differences in the time available for moulting. Eastern populations were characterized by a limited extent of feather moult that was additionally affected by migration distance and body mass. The longer migration distance in the Eastern Palearctic caused a generally less extensive moult while high body mass was correlated with a low difference in moult extent between the Western and Eastern Palearctic regions. These results highlight the importance of linking annual cycle processes at the organismal level to the specific environmental conditions within the distribution range of each species.